The Effect of Lemon Aromatherapy on Emesis Gravidarum in Pregnant Women in the First Trimester - Tuti Purwati; Nila Widya Keswara (Jurnal Rumpun Ilmu Kesehatan, 2026)
Emesis gravidarum is a common complaint among pregnant women in their first trimester that can interfere with daily activities, nutritional intake, and quality of life. One safe and easy-to-apply non-pharmacological intervention to reduce this complaint is lemon aromatherapy. This study aims to determine the effect of lemon aromatherapy on emesis gravidarum in pregnant women in their first trimester. The study used a quantitative approach with a quasi-experimental one-group pretest–posttest design. The study sample consisted of 30 pregnant women in their first trimester who were selected using purposive sampling. The intervention involved the administration of lemon aromatherapy through inhalation. The level of emesis gravidarum was measured before and after the intervention using an appropriate nausea and vomiting scale. Data analysis was performed using the Wilcoxon Signed Rank Test. The results showed a significant difference between the levels of emesis before and after lemon aromatherapy (p = 0.000). Before the intervention, most respondents experienced moderate to severe emesis, while after the intervention, the majority of respondents experienced mild emesis and no severe emesis was found. The conclusion of this study indicates that lemon aromatherapy has a significant effect in reducing gravidarum emesis in first trimester pregnant women and can be used as a supportive non-pharmacological therapy in antenatal care.